Distillers grains do not change carcass composition but change some fatty acids when added to finishing diet - Black, P.L.; Parsons, G.L.; Shelor, M.K.; Karges, K.K.; Gibson, M.L.; Dikeman, Michael E.; Smith, J. Scott; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Distillers grains are a by-product of ethanol production and have become increasingly available in recent years. Some research has revealed negative effects of distillers grains on quality and yield grades. Distillers grains contain substantial amounts of unsaturated fats and therefore could alter the ratios of saturated and unsaturated fats to achieve a more desirable composition in beef. Heterocyclic amines are the carcinogenic compounds released during high-temperature grilling of meat and would be increased if fat composition is changed. Our objectives were to evaluate effects of feeding distillers grains on carcass fatness, fatty acid profiles, and formation of heterocyclic amines.
Keywords: Beef; Cattle; Distillers grains